Sosialisasi Pemanfaatan Pekarangan Rumah Sebagai Sumber Kebutuhan Pangan Dan Tambahan Penghasilan Keluarga Kelurahan Kolang Nauli - Khairil Safli Pohan; Zafril Abdi Nasution (COVIT (Community Service of Health), 2023)
The objectives of implementing this community partnership program (PKM) service are 1) understanding of PKM in the midst of the Kolang Nauli Village community, 2) understanding in socialization in the midst of the Kolang Nauli urban village community, 3) understanding the importance of utilizing the yard of the house as a source of food needs and additional family income in Kolang Nauli village. The method of implementing the activities of utilizing the home yard as a source of food needs and additional family income includes several stages, namely: 1) Preliminary Stage, 2) Socialization and Audience Stage, 3) Final Evaluation Stage. The result of this activity is that the community can utilize and understand how important it is to use the yard as a source of food needs and additional family income in the Kolang Nauli sub-district. The PKM community service partner is Kolang Nauli Village, Kolang District, Central Tapanuli Regency. This program is carried out as an effort to broaden the community's insight into the use of yards as a source of food needs and additional family income. Keywords: Yard, Utilization, Source, Income